PERAN STANDAR PROSEDUR OPERASIONAL (SPO) DALAM MENJAMIN MUTU DAN KESELAMATAN PRAKTIK KESEHATAN DI RUMAH SAKIT - Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
Standard Operating Procedures (SOPs) are essential guidelines for ensuring the quality and safety of healthcare practices in hospitals. This study aims to examine the role of SOPs in improving service quality and patient safety through a review of literature from various scientific sources. The findings indicate that consistent implementation of SOPs can create a structured, efficient, and accountable work system, thereby minimising the risk of medical errors and enhancing service accountability. Additionally, SPO serves as a control tool in the monitoring, evaluation, and fulfilment of hospital accreditation standards. However, the effectiveness of SPO implementation is significantly influenced by factors such as healthcare staff compliance, management support, training, and the availability of adequate resources. Therefore, optimising SPO implementation requires the commitment of all hospital elements to achieve sustainable improvements in healthcare quality and safety.